Lobbying no Brasil: Profissionalizaç\~ao, estratégias e influência - Manoel Leonardo Santos; Wagner Pralon Mancuso; Marcello Fragano Baird; Ciro Antônio da Silva Resende (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The study analyzes data from an original survey conducted with representatives of public or private entities registered in the Brazilian Chamber of Deputies. The questions relate to three dimensions of the lobbying activity: its recent professionalization, strategies and repertoires of activities of these groups and, finally, the respondents' perceptions about their influence in the decision making process. The results point to a trend towards professionalization, a very broad repertoire of activities, but focused on the exchange and dissemination of information as the main asset of interest groups, and to an optimistic view regarding its capacity for parliamentary influence.
Keywords: Y8; 330; interest groups; lobbying; legislature